2009
DOI: 10.1111/j.1540-8175.2009.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Right Ventricular Systolic Dysfunction by Tissue Doppler‐Derived Isovolumic Myocardial Acceleration in Patients with Chronic Obstructive Pulmonary Disease

Abstract: TDI-derived RV IVA is a novel, noninvasive echocardiographic index which may be used in the assessment of subclinical RV dysfunction in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
3
19
0
4
Order By: Relevance
“…They did not observe a significant difference in RV echocardiographic indices between adult RA patients and controls [2]. Due to problems with the conventional echocardiographic measurements, TDI-derived ejectionphase myocardial velocities have gained in importance in evaluation of RV function [25]. In the present study, we have shown that the so-called ''forgotten chamber,'' the right ventricle, was also affected in children with JIA.…”
Section: Discussionsupporting
confidence: 48%
“…They did not observe a significant difference in RV echocardiographic indices between adult RA patients and controls [2]. Due to problems with the conventional echocardiographic measurements, TDI-derived ejectionphase myocardial velocities have gained in importance in evaluation of RV function [25]. In the present study, we have shown that the so-called ''forgotten chamber,'' the right ventricle, was also affected in children with JIA.…”
Section: Discussionsupporting
confidence: 48%
“…In other words, COPD mainly affects the structure and functions of the RV. The evaluation of RV functions in COPD patients is crucial because of the relationship between RV dysfunction and increased mortality [15,23]. Although both RV functions and BODE index predict increased mortality in COPD patients, the relationship between them has not been studied up to now (except for the individual components of BODE index).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, 2D echocardiography is the most frequently used noninvasive method for this evaluation. It is accompanied by important limitations, however, including the complex geometry of the RV, the predominantly longitudinal orientation of its myofibrils and poor echogenicity in COPD patients [15,23]. 2D-STE is a new technique whichpermits the differentiation of active motion from passive motion, independent of the Doppler angle of incidence, tethering effect and load dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Tayyareci et al (6) pointed out the importance of IVA in the early diagnosis of right ventricular systolic function defect in cases with mitral stenosis. Moreover, it has been found that IVA showed the deterioration in right ventricular functions much earlier than the other parameters (14,15). Also, in healthy subjects, IVA is unchanged following significant increases in preload and is regarded as a potential measure of contractility.…”
Section: Discussionmentioning
confidence: 99%